2018
DOI: 10.2147/dddt.s146556
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intra-meibomian gland injection of the anti-VEGF agent bevacizumab for the treatment of meibomian gland dysfunction with lid-margin vascularity

Abstract: PurposeTo investigate the efficacy of a novel treatment – intra-meibomian gland (MG) injection of the anti-VEGF agent bevacizumab – for MG dysfunction (MGD) with eyelid-margin vascularity.MethodsA total of 26 eyes from 13 patients diagnosed with MGD and eyelid-margin vascularity were included in our study. Patients received intra-meibomian gland injections of bevacizumab (150 μL, 2.5 mg/0.1 mL) at multiple sites with a 29 G needle where telangiectasia was severe. The Ocular Surface Disease Index (OSDI), tear f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…However, both groups exhibited significant improvements in dry eye symptoms and clinical signs, including corneal staining, meibum quality, meiboscore, and conjunctival redness. Our results are consistent with those of previous studies (11,18,19).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…However, both groups exhibited significant improvements in dry eye symptoms and clinical signs, including corneal staining, meibum quality, meiboscore, and conjunctival redness. Our results are consistent with those of previous studies (11,18,19).…”
Section: Discussionsupporting
confidence: 94%
“…The OSDI scores decreased significantly from week 1 to month 3, although there were no between-group differences. Previous studies of bevacizumab therapy in DED and MGD (11,18,19) showed significantly improve dry eye symptoms. Improvements in OSDI scores may be explained by decreases in corneal staining and lid margin inflammation and by improvements in tear film stability.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Significant improvements in the positivity rates and MMP-9 expression levels were observed, which could explain improvements in the clinical signs and symptoms. In one study that evaluated the effect of an intra-MG bevacizumab injection on the lid margin telangiectasia in MGD patients, the lid margin telangiectasia was improved significantly, subsequently resulting in improvements in TBUT, corneal staining scores, and symptoms [ 33 ]. In accordance with previous studies on IPL, Schirmer’s test was not improved in the present study [ 23 , 30 , 34 ].…”
Section: Discussionmentioning
confidence: 99%